Fiduciary Remedies - Bray, Samuel L. (The Oxford Handbook of Fiduciary Law, 2019)
This chapter offers an overview and analysis of fiduciary remedies. The remedies considered are accounting for profits, constructive trust, equitable compensation, injunction, the unwinding remedies (e.g., rescission), and the supervisory remedies (e.g., instruction, removal). One point of emphasis is the close relationship between fiduciary duties and fiduciary remedies. The chapter also distinguishes the remedies of fiduciary law from those of agency. In addition, the chapter considers three major unsettled questions. First, are the remedial aims of fiduciary law distinct from tort and contract? Second, how should judges and scholars think about fiduciary remedies in light of the distinction between law and equity? Third, is punishment of an erring fiduciary a legitimate aim for fiduciary remedies?